Research on bra component design and perceptual image prediction - Fang, Fang; Hu, Caili; Yan, Ting Ting (International journal of clothing science and technology, 2021)
PurposeThe purpose of this paper is to apply the theory of perceptual image to clothing, study the effect of bra components on the perceptual image of Chinese female consumers aged 18 to 27, explore the relationship between them, promote the computer-aided bra design to be more rapid and accurate and meet consumer's needs better.Design/methodology/approachIn this paper, cognitive psychology and mathematical analysis methods were used, and two experiments were conducted. A reaction time experiment was conducted based on 3D virtual bra samples, proving that bra components have an effect on the consumer's perceptual image and obtaining a revised bra component design indicator system by multi-dimensional Scaling (MDS). A projection experiment was conducted to study what kind of relationship exists between the two, and a prediction model was constructed by the quantitative I-class theory.FindingsIt is found that bra components have an effect on perceptual image of Chinese female consumers aged 18 to 27. A total of five important components (cup area, center front height, torso width, side wing width and center back shape) that affect the consumer's perceptual image were identified by MDS and references analysis, and then a bra perceptual image space composed of five pairs of words was constructed by subjective evaluation and cluster analysis. What is more, a prediction model was obtained by the quantitative I-class theory; after testing, the model can visually and effectively predict consumer's perceptual image according to bra components indicators, which provide a convenience for the positive design of bras.Research limitations/implicationsIn this article, the authors just studied bra components, but did not take fabric, color and other factors that also affect the perceptual image into consideration. Further research can use this method to study other important influential factors as well as their comprehensive impact. Also, the subjects are Chinese young women; consumers of other age or from other countries are not involved, and more extensive research can be done in the future.Practical implicationsThe bra component indicator system can help to build a more systematic and clearer bra design library, which provides convenience for designers to search and use them quickly, improving the efficiency of bra design. The prediction model is also helpful to bra designers and companies. When they already design a bra, they can use this model to predict consumer's perceptual image, thus carry out more accurate market positioning and promotion. When they want to satisfy consumers or design a specific effect, they can also refer to this model to reverse design of components. In general, the outcomes of this paper can help companies to quickly establish a computer-aided bra design system, which is conducive to designers to accurately design and better meet market's needs, and the method is also a good attempt to apply the theory of perceptual image in psychology to clothing and can be extended to other relevant fields in the future.Originality/valueBased on cognitive psychology, this paper attempts to apply the theory of perceptual image in psychology into clothing and takes bra as an example to study the relationship between bra components and consumer's perceptual image. The prediction model constructed here is conducive to the development of bra design and to meet personalized needs of consumers. This method can also be extended to other fields in the future.